2008
DOI: 10.1073/pnas.0709698105
|View full text |Cite
|
Sign up to set email alerts
|

Cassandraretrotransposons carry independently transcribed 5S RNA

Abstract: We report a group of TRIMs (terminal-repeat retrotransposons in miniature), which are small nonautonomous retrotransposons. These elements, named Cassandra, universally carry conserved 5S RNA sequences and associated RNA polymerase (pol) III promoters and terminators in their long terminal repeats (LTRs). They were found in all vascular plants investigated. Uniquely for LTR retrotransposons, Cassandra produces noncapped, polyadenylated transcripts from the 5S pol III promoter. Capped, read-through transcripts … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
152
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 127 publications
(161 citation statements)
references
References 77 publications
9
152
0
Order By: Relevance
“…Finally, our work supports the conclusions of various recent reports (Rooney and Ward, 2005;Kalendar et al, 2008;Vierna et al, 2009;Freire et al, 2010;Perina et al, 2011;Vierna et al, 2011;Vizoso et al, 2011), in which it was shown that the evolutionary patterns of 5S rDNA in animals are complex and cannot be explained only in the light of concerted evolution. Birth-and-death processes, selection, homogenizing mechanisms typically involved in concerted evolution Figure 7 Evolutionary-conserved linkages of 5S rRNA and mir-562.…”
Section: Resultssupporting
confidence: 80%
See 1 more Smart Citation
“…Finally, our work supports the conclusions of various recent reports (Rooney and Ward, 2005;Kalendar et al, 2008;Vierna et al, 2009;Freire et al, 2010;Perina et al, 2011;Vierna et al, 2011;Vizoso et al, 2011), in which it was shown that the evolutionary patterns of 5S rDNA in animals are complex and cannot be explained only in the light of concerted evolution. Birth-and-death processes, selection, homogenizing mechanisms typically involved in concerted evolution Figure 7 Evolutionary-conserved linkages of 5S rRNA and mir-562.…”
Section: Resultssupporting
confidence: 80%
“…They appear to be the result of stochastic processes within genomes with no effect on fitness, even though this has not been demonstrated (see Drouin and Moniz de Sá (1995) for a review). Interestingly, 5S rDNA repeats can show different organization modes in the same species (Little and Braaten, 1989), and their transposition could be frequent within genomes, as reported by Drouin and Moniz de Sá (1995); Kalendar et al (2008); Cohen et al (2010).…”
Section: Introductionmentioning
confidence: 68%
“…Drouin and Moniz de Sá (1995) hypothesised that a 5S rDNA transposition could be produced at the DNA level mediated by extrachromosomal circular DNA or by an RNA intermediate. Interestingly, recent surveys have given support to both hypothesis (Kalendar et al, 2008;Cohen et al, 2010). Similarily, Rooney and Ward, (2005) hypothesised that 5S rDNA was capable of multiplying and integrating into other areas of the genome through a process the same as, or similar to, retroposition, in filamentous fungi.…”
Section: Upstream Elements Internal Regulatory Regions and Downstreamentioning
confidence: 81%
“…The divergent number and physical location of the 5S rDNA genes could be caused not only by chromosome rearrangement, including inversions, duplications, deletions and translocations (Hanson et al 1996;Thomas et al 1996;Raskina et al 2008;Wang et al 2013), but also by transposon-mediated transposition events (Raskina et al 2004;Altinkut et al 2006;Datson and Murray 2006). Several cases of 5S rDNAderived sequences being found within transposable elements have been reported (Kapitonov and Jurka 2003;Kalendar et al 2008). By contrast, loss of rDNA loci during evolution has occurred in Brassicaceae and Rosaceae (Mishima et al 2002;Hasterok et al 2006;Liu and Davis 2011).…”
Section: Karyotype Characterization After Dapi Stainingmentioning
confidence: 99%